Resilience of organic rice and supermarket value chains during the COVID-19 pandemic the case of the global organic wellness corporation - Tacubanza, Elaine; Barreiro, Ernest; Abrina, Tara; Copacio, Jane Lynn (2023)
With the widespread growth of healthy lifestyle...